Executive Committee Minutes 2021-02-11 - Academic Senate:::::::::
Approval of Agenda, items added – Approved. Minutes of 2/4/2021 – Approved. Chair Report. President Report. Provost Report. Statewide Senators Report. Vice President of Administration and Finance Report. Vice President for Student Affairs Report. Associated Students Rep. From FSAC: RTP documents for discussion at Senate – approved for Senate agenda. Faculty Eligible for Emeritus Status for Spring 2021 – Gregory Roberts – approved for Senate consent calendar. Posthumous degree request for Alondra Bandt and posthumous certificate request for Luis Cid approved for Senate agenda. By-Law Change: Membership on URTP – approved for Senate agenda. From EPC: Changes to the Academic Calendar – not approved for Senate agenda, return to EPC. Senate agenda approved.